Integrasi Teori Komunikasi Difusi Inovasi Dalam Pelatihan SPAB (Satuan Pendidikan Aman Bencana) Study Pengabdian Masyarakat Internasional - Muhamad Khalid Iswadi; Alfiatmi Laelatunnufus; Nur Fitrianingsi; Siti Julaikha (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Natural disasters and the impacts of climate change threaten the sustainability of the education sector worldwide, including in Indonesia. This study aims to integrate the innovation diffusion communication theory into SPAB (Safe School Program) training to enhance disaster preparedness in educational institutions at national and international levels. Training materials rooted in local wisdom, such as disaster preparedness calendars and emergency kits, were employed to support the application of innovation diffusion theory which encompassing five stages: knowledge, persuasion, decision, implementation, and confirmation. The findings reveal that the innovation diffusion-based approach effectively fosters the adoption of disaster mitigation measures across various educational institutions. However, challenges such as cultural differences, limited resources, and inter-institutional coordination must be addressed through collaborative and adaptive strategies. This study recommends strengthening local wisdom-based materials, improving cross-sector coordination, and conducting continuous program evaluations to ensure the success of SPAB training.